Sucess\~ao nas fazendas familiares: Problemas e desafios - Walber Machado de Oliveira; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– Family farms - whether small, medium-sized or large - remain as the largely predominant unit of production in agriculture throughout the world. This work examines the succession process in such entrepreneurships, through which the accumulated knowledge in management and the business assets are transmitted from generation to generation. The interlacing between family and business objectives is discussed, as well as the processual feature of the intergenerational transition. Critical aspects pertaining to its unfolding are pointed out, such as the importance of an analysis of the business financial and economical viability and the communication over themes like the fairness or equanimity in the distribution of assets.
Keywords: Q1; D1; D23; 330; family farms; succession; management; agribusiness